2022
DOI: 10.1039/d1fo03616e
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of procyanidin B2 on adriamycin-induced nephrotic syndrome mice: the multi-action mechanism for ameliorating glomerular permselectivity injury

Abstract: Despite considerable advances in prevention, diagnosis, and therapy, nephrotic syndrome (NS) remains a significant cause of high morbidity and mortality globally. As a result, there is an urgent need to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 162 publications
0
5
0
Order By: Relevance
“…[53,54] The primary mechanisms of Doxinduced kidney damage include oxidative stress, inflammation, and apoptosis. [55] Nephrotoxicity induced by Dox (at a cumulative dose of 20 mg/kg) was assessed by evaluating several parameters in serum and renal tissues. Rats receiving Dox experienced glomerular filtration disruption, which led to an increase in levels of serum urea and creatinine and a decrease in albumin; alteration in these biochemical parameters indicates the severity of the renal failure and glomerular damage, which is consistent with earlier research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[53,54] The primary mechanisms of Doxinduced kidney damage include oxidative stress, inflammation, and apoptosis. [55] Nephrotoxicity induced by Dox (at a cumulative dose of 20 mg/kg) was assessed by evaluating several parameters in serum and renal tissues. Rats receiving Dox experienced glomerular filtration disruption, which led to an increase in levels of serum urea and creatinine and a decrease in albumin; alteration in these biochemical parameters indicates the severity of the renal failure and glomerular damage, which is consistent with earlier research.…”
Section: Discussionmentioning
confidence: 99%
“…[ 53,54 ] The primary mechanisms of Dox‐induced kidney damage include oxidative stress, inflammation, and apoptosis. [ 55 ]…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed the protective effects of avonoids on the kidneys. [41][42][43] In our sensitivity analysis, we did not observe evidence of the positive effects of the six subcategories of avonoids in non-obese individuals with concurrent CKD, suggesting that the contribution to survival in this group may be due to total avonoid intake. One possible explanation is a study conducted in Korea that found total avonoids in Epimedium koreanum Nakai alleviated chronic renal failure by promoting AMPK activation.…”
Section: Discussionmentioning
confidence: 99%
“…A transmission electron microscope (TEM; HT7800; Hitachi, Japan) was used to evaluate ultrastructural changes in the kidney. The protocol of TEM analysis is in accordance with our prior reports …”
Section: Methodsmentioning
confidence: 99%
“…The protocol of TEM analysis is in accordance with our prior reports. 36 2.6. Prussian Blue Staining.…”
Section: Histopathological Analysis and Ultrastructuralmentioning
confidence: 99%